Two distinct Kantian perspectives on the foundation of human rights - Morelli, Jacopo (Studia Kantiana, 2025)
United Nations documents establish dignity as the cornerstone of human rights, asserting that these rights “stem from the inherent dignity of the human person,” as articulated in the International Covenants on Civil and Political Rights (1966). Within this context, human dignity is viewed as an intrinsic value inherent in every human being, serving as the foundation for the moral obligation to respect one another. While many scholars turn to Immanuel Kant for a philosophical analysis and validation of this concept, there is a question of consensus among Kantian scholars on this interpretation. This article aims to explore how two perspectives, both claiming Kantian paternity – the Dignity approach and Kantian constructivism – arrive at differing conclusions regarding the foundational nature of human rights. I will focus respectively on Luigi Caranti’s Dignity approach and Oliver Sensen’s constructivist reading, to show how the two frameworks deploy different conceptions on how dignity can truly ground human rights. In the end, I will also suggest a potential common ground between the two perspectives.